Strategi Pengembangan Pemasaran Produk PT. East Indo Fair Trading (East Bali Cashews) Denpasar, Bali di Era Pandemi Covid-19 - MILLENIA, MARIA ANGELA; ANTARA, MADE; SUAMBA, I KETUT (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism), 2023)
Product Marketing Development Strategy of PT. East Indo Fair Trading (East Bali Cashews) Denpasar, Bali in the Era of the Covid-19 Pandemic . The Covid-19 pandemic that has occurred since 2020 has caused a decline in the sales of PT. East Indo Fair Trading (East Bali Cashews), so that this company can increase sales again in the pandemic era, it is necessary to formulate an appropriate marketing strategy. This study aims to formulate general strategies, alternative strategies, strategic priorities and appropriate development programs to be applied to the product marketing process of PT. East Indo Fair Trading (East Bali Cashews). The strategy determination process is carried out using the IE, SWOT, and QSPM matrix. Based on the results of the IE matrix analysis, PT. East Indo Fair Trading (East Bali Cashews) is in cell I which indicates a strong and potential company, so the most suitable strategy is a growth and development strategy. The results of the SWOT analysis obtained five alternative strategies, namely: a) Maximizing the use of digital marketing b) Making land leased by PT. East Indo Fair Trading (East Bali Cashews) as a family tourism area c) Increase marketing by expanding the marketing network d) Maintaining the quality and taste of the product e) Provide various promotions. The strategic priority obtained through QSPM Analysis is to maximize the use of digital marketing. Suggestion for PT. East Indo Fair Trading is this research can be used as a reference for companies to make decisions regarding future marketing strategies and carry out priority strategies that have been obtained through this research.